Fish target strength using sonar - Sunardi; Raja Bidin Raja Hassan; Nadzri Seman; Adil mohd; Jafri Din; Proceeding of the International Conference on Robotics Vision Information and Signal Prpcessing ROVISP 2007 (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL